Studi Kualitas Pelayanan Apotek Ditinjau dari Tingkat Kepuasan Konsumen di Kecamatan Sumbersari Jember (Study of Pharmacy Quality Service According to Costumer Satisfaction Levels in Sumbersari Jember) - Desinta Sylviana Putri Diarti; Prihwanto Budi S; Wiratmo Wiratmo (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Pharmacy is one of many place that provide products and services linked to customer satisfaction. To increase the quality of pharmacy services, we need know costumer satisfaction levels about the pharmacy services they received currently. The aim of this research was to know customer satisfaction level of pharmacy services. This was the descriptive type research with purposive sampling. The sampling method was proportional stratified random sampling. Samples were 100 respondents from 13 pharmacies. Data obtained by distributing questioner that measure the level of satisfaction based on five dimensions of satisfaction that is tangible, responsiveness, reliability, assurance and empathy. The data then was analyzed using correlation value, by comparing the perception of reality and hope which was showed in Cartesian diagram. The results showed that consumers have a good perception of the pharmacy service on all the dimensions indicated on the interpretation of high-value, which means the level of satisfaction is very satisfied. Keywords: satisfaction, pharmacy services, Jember